Benefits of a Product's Industry 4.0 Compliancy - Koskinen, Kalle (My University, 2023)
The latest industrial revolution, the fourth one labeled Industry 4.0, has been ongoing for over a decade. Still, the topic seems to be surrounded by ambiguity with lacking some of the details defining what it really means, what is the purpose of the Indsutry 4.0? Inspired by a cloud integration project implemented by Cryotech Nordic for an Italian company in autumn 2021, the aim of this thesis is to answer some of the questions that arose during the project related to Industry 4.0 by looking at the issue from the perspective of product features, while discussing the benefits that different stakeholders seek and obtain from the implementation of Industry 4.0 technologies and systems. The thesis utilises two methods for its two research questions, one where national Industry 4.0 initiatives and known Industry 4.0 products are studied and another where a literature review is conducted to find answers from group of articles. The outcome of the thesis is a construction of a Minimum Viable Product model and a categorisation for the benefits and for stakeholders receiving the benefits from the Industry 4.0 implementations with a statistical distribution of the found benefits into these categories.
Keywords: industry 4.0, stakeholder, benefits, iot, cloud computing, digitalisation